Ethical issues in research on substance‐dependent parents: The risk of implicit normative judgements by researchers. (18th September 2018) - Snoek, Anke; Horstkötter, Dorothee
Abstract: When doing research among vulnerable populations, researchers are obliged to protect their subjects from harm. We will argue that traditional ethical guidelines are not sufficient to do this, since they mainly focus on direct harms that can occur: for example, issues around informed consent, fair recruitment and risk/harm analysis. However, research also entails indirect harms that remain largely unnoticed by research ethical committees and the research community. Indirect harms do not occur during data collection, but in the analysis of the data, and how the data is presented to the scientific and wider societal community. Highly stigmatized research subjects, like substance‐dependent parents, are especially at risk of encountering indirect harm, because the prejudice against them is so persistent. In this paper we discuss two forms of indirect harm. First, researchers have to be aware how their results will be preceived by society. Even when subjects are presented in an objective way, further, out of porportion stigmatization can occur. Researchers sometimes try to counteract this by whitewashing their results, at the risk of downplaying their respondents' problems. The second risk researchers face is that their own normative judgements influence how they question such parents, report results and interpret statements. Researchers' own normative judgements may influence the way they present their subjects. This article reviews a broad range of research that exhibits such indirect harms, discussing how and why indirect harms occur and formulating corresponding recommendations on how to prevent them.